The Mediating Role of Competitive Advantage on Marketing Innovation and Business Performance in Micro and Small Restaurants in Western Batangas - Sanchez , Ma. Luz (Journal of Interdisciplinary Perspectives, 2025)
This study addresses the gap in understanding how marketing innovation influences competitive advantage and business performance in micro and small-scale restaurants in Western Batangas. Specifically, it examines the roles of market orientation and product innovation in contributing to competitive advantage, characterized by value, rarity, inimitability, and non-substitutability. The objectives were to analyze the effects of marketing innovation on competitive advantage and business performance, while also exploring the mediating role of competitive advantage. Employing an Explanatory Sequential Mixed-Method design, the research commenced with the quantitative analysis of data gathered from 159 restaurant owners and managers using a self-constructed questionnaire. Statistical tools, including frequency analysis, percentages, means, simple linear regression, and the Sobel Test, were utilized. This was followed by qualitative insights obtained through Focus Group Discussions with five participants, analyzed using Thematic Analysis. Results showed a concentration of restaurants in Balayan, Nasugbu, and Calatagan, with most operations lasting less than ten years and employing between 1 and 99 staff. Findings indicated that both market orientation and product innovation have a positive impact on competitive advantage; however, competitive advantage did not significantly mediate the relationship between marketing innovation and business performance. The Sobel test and qualitative interviews confirmed this. The study concludes that marketing innovation enhances the performance of micro and small-scale restaurants indirectly by providing a competitive advantage. A concise business manual was developed to provide actionable strategies for restaurant owners aimed at improving product offerings, services, and overall competitiveness in the market.